(untitled) (The Pakistan Development Review, 1991)
Employment and manpower development (E&MD) considerations are appearing in Pakisan’s development plans since the Fifth Five-Year Plan. These considerations, though improving upon earlier neglect and at times indifference, however, did not go beyond mere projection exercises-themselves point of considerable debate 1 - and calculations of employment impact of investment plans and targeted sectoral growth rates.2 These plans (manpower plans) besides being devoid of education and training programmes also have no integration with the development plans, a prerequisite for a meaningful development exercise. A general lack of awareness amongst the planners and policy-makers about the vital links between the E&MD and the development only partly explains the existing scenario. Absence of a reliable and adequate data base on E&MD related variables appear to be an important constraint for undertaking any meaningful exercise of employment and manpower planning. Existing institutional mechanism of the Labour Market Information System (LMIS) in Pakistan is not responding adequately in addressing its three functions, namely (i) Labour Market Information, (ii) Labour Market Diagnosis, and (iii) Labour Market Intermediation.3 The first two functions are required to provide detailed information on E&MD-related variables a subject of discussion of this paper. This non-responsiveness is mainly attributable to low E&MD considerations in earlier policy formulations.